A Study on the Impact of Social Media on the Personal Values of Higher Secondary School Students in Raipur District (International Journal of Environmental Sciences, 2024)
The present study investigates "the impact of social media on the personal values ​​of students in Higher Secondary Schools of Raipur District." For this research, schools at the higher secondary level were selected using the random sampling method. A sample comprising 100 students (50 boys and 50 girls) was selected. For data collection, the researcher utilized two standardized instruments: the 'Social Media Scale,' developed by Balwinder Singh and Surjit Lal, and the 'Personal Values ​​Scale,' developed by Archana Dubey and Mahendra Patidar. The survey method was employed for this research study. The research findings revealed that a significant difference was observed regarding the impact of social media on the personal values ​​of male students in higher secondary schools. Similarly, a significant difference was found regarding the impact of social media on the personal values ​​of female students in higher secondary schools. Overall, a significant difference was observed regarding the impact of social media on the personal values ​​of students in higher secondary schools.